“I HOPE THIS HURTS.” — Rhetorics of Rape in "Mouthwashing" Digital Game - Katarzyna Matlas (Zagadnienia Rodzajów Literackich, 2025)
This paper examines how Mouthwashing (2024), an indie horror game, constructs a space where horror aesthetics and agency-related mechanics converge, allowing players to engage with sensitive social issues such as sexual violence. By restricting player control and integrating classic horror elements — including an unreliable narrator and intentional narrative gaps — the game elicits feelings of helplessness and complicity, mirroring the mechanisms of sexual violence from the perspectives of both the aggressor and the enabler. Drawing on agency theory (Harrell, Zhu 2009; Wardrip-Fruin et al. 2009) and horror aesthetics, this study explores how Mouthwashing employs grotesque imagery, hallucinations, and constrained player choice to expose power dynamics and rape myths. The game illustrates the consequences of patriarchal violence within a confined group through its fragmented narrative. Mouthwashing exemplifies the capacity of indie horror games to employ subversive storytelling and innovative game mechanics to address taboo subjects, highlighting the potential of interactive media to provoke critical reflection on agency, complicity, and systemic abuse.